A DNA barcode reference library of Portuguese mosquitoes - Madeira, S. (2022)
Mosquitoes are important biological vectors of pathogens and species identification in all life stages is the first step for effective monitoring and control of mosquito-borne diseases. Molecular methods for species identification have been developed over the last years to overcome the limitations of the taxonomic identification based on morphology. DNA barcoding, using a fragment of the mitochondrial cytochrome oxidase I (COI) gene, can be used for species identification but a reliable and comprehensive reference database of verified sequences is required. In this study, we aimed to generate a DNA barcode reference library for the identification of mosquito species from Portuguese mosquito fauna, including most relevant vector species. Mosquitoes captured under the National Vector Surveillance Program (REVIVE) were processed for DNA extraction, COI gene fragment amplification and sequencing. Nighty-eight barcode sequences were obtained, representing 26 species and 6 genera. Sequences were submitted to GenBank and BOLD and were used for validation of phenetic classification. Barcode Index Number (BIN) assignment and Automatic Barcode Gap Discovery (ABGD) were used and clustered COI sequences into twenty-five molecular operational taxonomic units (MOTUs). This is the first comprehensive study that combines morphological and molecular identification of most mosquito species present in Portugal aiming to offer a reliable framework for mosquito species identification.